Decision support and data warehouse systems - Mallach, Efrem (Irwin McGraw-Hill, 2000)
"Decision Support and Data Warehouse Systems" ties the more traditional view of decision support to the rapidly evolving topics of database management and data warehouse. As organizations move quickly into networked-based environments, the nature of decision support tools has become increasingly complex. These tools are now used collaboratively and the use of data warehousing mechanisms will be a critical success factor for the survival of many organizations. This new book provides a strong foundation for the use of models within the context of building and using decision support systems, and it will focus on multi-dimensional databases and client/server computing.